Amino acid infusion in oligohydromnios and increase in AFI and impact on perinatal outcome - Sunil, Isha; Sunitha, Chejerla; Kaur, Harkirat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Decreased amniotic fluid is related to adverse maternal and perinatal outcomes. The purpose of this study was to evaluate the role of amino acid infusion in patients of oligohydromnios and compare the perinatal outcome in the two groups. Methods: This study was conducted in the Department of Obstetrics and Gynaecology, ASCOMS Hospital, Jammu for a period of one year from October 2017 to September 2018. A total of 50 women with AFI <8 cm were enrolled in the study . They were divided into two groups of 25 each. Group A were given amino acid infusion and Group B were not given any intervention. These were compared for increase in AFI and perinatal outcome. Results: In the present study, the gain in AFI in Group A was 2.32 ± 0.67 and in group B was 1.32 ± 1.03 which was statistically significant. The perinatal outcome was better Group A compared to Group B with decreased incidence of meconium stained liquor, low birth weight, low APGAR scores and NICU admissions and increase in vaginal deliveries as compared to caesarean sections. Conclusions: The present study suggests that parentral transfusion of amino acid in cases of oligohydromnios significantly increases the AFI of the patient and decreases the incidence of caesarean sections, meconium stained liquor, low APGAR scores and NICU admissions.